THE RESEARCH AND EVALUATION OF ROAD ENVIRONMENT IN THE BLOCK OF CITY BASED ON 3-D STREETSCAPE DATA - L. Guan; Y. Ding; J. Ge; H. Yang; X. Feng; P. Chen (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences, 2018)
This paper focus on the problem of the street environment of block unit, based on making clear the acquisition mode and characteristics of 3D streetscape data，the paper designs the assessment model of regional block unit based on 3D streetscape data. The 3D streetscape data with the aid of oblique photogrammetry surveying and mobile equipment，will greatly improve the efficiency and accuracy of urban regional assessment, and expand the assessment scope. Based on the latest urban regional assessment model, with the street environment assessment model of the current situation, this paper analyzes the street form and street environment assessment of current situation in the typical area of Beijing. Through the street environment assessment of block unit, we found that in the megacity street environment assessment model of block unit based on 3D streetscape data has greatly help to improve the assessment efficiency and accuracy. At the same time, motor vehicle lane, green shade deficiency, bad railings and street lost situation is still very serious in Beijing, the street environment improvement of the block unit is still a heavy task. The research results will provide data support for urban fine management and urban design, and provide a solid foundation for the improvement of city image.